All-cause mortality, cardiovascular mortality, major cardiovascular events and hypoglycaemia of patients with diabetes onset at an older age: results from the 10-year nationwide cohort study. (30th September 2021) - Chou, Ming-Yueh; Huang, Shih-Tsung; Liang, Chih-Kuang; Peng, Li-Ning; Lin, Yu-Te; Hsiao, Fei-Yuan; Chen, Liang-Kung
Abstract: Background: Longitudinal adverse outcomes are unclear among adults with diabetes according to the age of onset. Objective: To investigate the longitudinal diabetes-related outcomes in adults with new-onset diabetes stratified by age. Design: Retrospective cohort study. Setting: Taiwan National Health Insurance Research Database claims data from 2000 to 2015. Subjects: In total, 115, 751 participants aged ≥40 years with new-onset diabetes in 2003 were recruited and stratified by the ages 40–64 (64.3%), 65–74 (21.2%), 75–84 (11.8%) and ≥85 years (2.7%) at the time of diagnosis. Methods: Time-varying multivariate Cox proportional hazards model adjusted for covariates was used to examine the associations between the ages of the patients at diabetes onset and the outcomes of interest [all-cause mortality, cardiovascular (CV) mortality, major cardiovascular events (MACE) and hypoglycaemia] during a 10-year follow-up period. Results: The results showed that compared with those patients aged 40–64 at diagnosis, patients with older-onset diabetes had significantly higher comorbidities ( P  < 0.01) and a higher diabetes severity ( P  < 0.01). Patients with older-onset diabetes had a higher risk of all-cause mortality [adjusted hazard ratio (aHR) 2.28, 4.48 and 10.07 in 65–74, 75–84 and ≥85 years old, respectively], CV mortality (aHR = 2.82, 6.06 and 15.91), MACE (aHR = 2.19, 3.01 and 4.15) and hypoglycaemia (aHR = 2.41, 3.59 and 4.62) than patients aged 40–64 during a 10-year follow-up period. Conclusions: Patients with diabetes onset at an older age was associated with increased risks of all-cause mortality, CV mortality, MACE and hypoglycaemia after adjusting for the severity of diabetes and anti-diabetic treatment.